A práxis na formação de uma humanidade nova: contradições, avanços e limites - Nobre, Iziane Silvestre (2021)
This thesis aims to investigate the category of praxis and its contribution to the formation of a new humanity, based on the theoretical and practical contributions formulated and experienced in the period of the Russian Revolution. Starting the discussion on the theoretical basis of Marx and Engels, we will conceptualize the category of praxis and present the conceptual obscurity between work and praxis, following the reflections of Barata-Moura (2010), Lukács (2013), Marx and Engels (2007), Sousa Junior (2010), Vázquez (2011), among others. The methodological path follows the prism of discussing the praxis between the duty to be and the future, part of an ontological perspective that is inserted within the mediations between the old and the new man, whose interactions between the various social praxis have the responsibility of not just raising the potentially revolutionary subject and transforming it into an effective revolutionary, as well as supporting the conception that it is not enough just to seize power, after that moment, it is necessary to build other mediations that require a wide change in habits, attitudes , customs, helping to build a new morality and a new ethics, guided by the principle of a humanity devoid of the yoke of the exploitation of man by man. In this sense, this thesis focuses on the category of revolution, taking it as a pedagogical perspective, because, as we transform objective reality, a new subjectivity is forged within the contradictions of a society in transition. Such categories find validity in the historical process, more precisely in the period of the Russian Revolution, for this reason, our study looks at history in order to ascertain the advances and limits of the revolutionary process. In this historical analysis, we will present the pre-revolutionary scenario, whose social formation of the different revolutionary groups in Tsarist Russia already demonstrated the presence of a subjectivity based on human emancipation, in this sense, it is inevitable not to touch the controversy between Marxists and Narodniks (populists) Russians), at the heart of the debate was about the possibility of a revolutionary process taking place on the periphery of capitalism. In addition, we will study the impact of the revolution on socioeconomic relations, gender and the attempt to form new humanity under the effervescence of a movement that screamed for a new world while trying to survive the ruins of the old society.